Contents of folates in edible mushrooms commercialised in the city of Campinas, São Paulo, Brazil - Furlani,Regina Prado Zanes (2007)
In this study, folates were evaluated in the main species of mushroom cultivated in Brazil. The species analysed were Agaricus bisporus (button mushroom), Lentinula edodes (shiitake) and Pleorotus ostreatus (shimeji). The five main forms of folate found in foods were determined: tetrahydrofolic acid (THFA), 10-methyl folic acid (10MFA), 5-methyl tetrahydrofolic acid (5MTHFA), 10-formyl folic acid (10FFA) and 5-formy tetrahydrofolic acid (5FTHFA). The methodology employed used extraction with phosphate buffer, clean up with trichloroacetic acid and separation of the vitamins by high-performance liquid chromatography, with simultaneous ultraviolet and fluorescence detection. The results obtained for total folate were 551 to 1404 µg.100 g -1 for the button mushroom, 606 to 727 µg.100 g -1 for shiitake and 460 to 1325 µg.100 g-1 for shimeji. The data showed that mushrooms could be considered as sources of folates and that their contribution of these vitamins to the diet was meaningful.